Kebijakan Perlindungan Hukum Terhadap Anak Pelaku Tindak Pidana - Endang Sutrisno; Yondri Yondri (Faculty of Law, Universitas Pekalongan, 2017)
The protection that has been imposed by law concerning the rights and obligations of human being as the subject of law in its interaction with other human being and its environment so that it can take legal action. Child protection in Law No. 35 of 2014 on Child Protection is defined as all activities for the protection and protection of children and the rights of children to live, grow, develop and properly in accordance with the dignity and dignity of humanity and get sanction from violence and disk . This paper discusses the law of a child who is full of laws. The acquisition of the load contained in the content of positive legal legislation is the right of every child, the embodiment for the children, building justice in society, for the achievement of the rights of the child. Special protection of children who are full of law in the criminal law domain for children who are victims of criminal acts, flee and offenders.Keywords: Legal Protection, Child Rights